Promoting intercultural competence through movie watching and acting rehearsal: a case study of advanced L2 students in higher education - Lee, Seung Chun (Cambridge Scholars Publishing, 2012)
This study primarily examines the effects of intensive acting performances consisting of dramatic dialogues on intercultural competence of advanced L2 students in higher education. Eighteen groups of pre-service English teachers selected one of their all-time favourite movies and chose a few scenes (15 to 25 minutes) which include intriguing conversations or intelligent arguments or poignant anecdotes. Each group produced videotaping of their performance after intensive rehearsals consisting of ‘cloning’ of the original actors or personal improvisation of their pronunciation. They provided introspective data on the selection processes for the movie/scenes and the rehearsal processes and the changes of their perspectives. Their dramatic dialogue practices stemmed from the entertainment merits, linguistic benefits and intercultural potential of selected movies and gave them greater fluency in oral delivery as the outcome of increasing familiarity with the text after intensive rehearsals of dramatic dialogues. However, the students believed that they enhanced more intercultural competence than linguistic proficiency. As such, their verbal reports highlighted the effectiveness of dramatic dialogue practices on increasing the spoken L2 skills as well as enhancing intercultural competence of students in higher education, which embodies the purpose of our education. The results support using the dramatic dialogues of movies is an invaluable resource of the cultivation for intercultural competence that has a positive effect on students’ overall communicative competence in its truest sense.